Use of Chorionic Villous Sampling for Prenatal Diagnosis of Beta Thalassaemia: Attitudes and Practices of Parents - Sundas Ali, Asfa Zawar , Samina Tufail Amanat , Shahzad Ali Jiskani ,Aliena Sohail ,Humaira Rizwan, Sundas Ali, Asfa Zawar , Samina Tufail Amanat , Shahzad Ali Jiskani ,Aliena Sohail ,Humaira Rizwan (Journal of Rawalpindi Medical College, 2017)
To assess the attitudes and practices of parents of Beta-Thalassaemia Major children regarding Chorionic Villous Sampling (CVS), as prenatal diagnosis in subsequent pregnancies. Methods: In this cross-sectional study a pre-designed questionnaire was used to evaluate the socio-demographic profile and attitudes of parents of 210 registered thalassaemic children, regarding CVS.Only those parents who had one or more pregnancies after the index case were included in the study. Results were entered and analyzed on SPSS version 20. Results: After the index case, 36.2% parents underwent CVS in all subsequent pregnancies . The common reasons not to utilize this facility were lack of knowledge (47.7%), careless attitude (41.7%), family pressure (4.4%) and financial issues (1.5%). Religious reason was not found in any of the cases. Majority of the families (54.3%) belonged to lower middle class financial status. There was a significant association between CVS practice and educational level of the mother and genetic counselling at the time of diagnosis of index case. In future pregnancies, 52.8% parents had no planning, while 15.7% showed interest in undergoing CVS in next pregnancies. Conclusion: Despite the availability of CVS in the country, very few families had opted for it; the major reasons being lack of knowledge, careless attitude and family pressure. As against the common thought, religious reason was not a significant factor.